Investigating the role of online initial trust in explaining the adoption intention of internet banking services. (24th March 2021) - Aljaafreh, Ali; Al-Hujran, Omar; Al-Ani, Ahmed; Al-Debei, Mutaz M.; Al-Dmour, Nidal
Online initial trust is one of the impediments that affect the adoption of new information technology (IT) innovations; therefore, improving customer's initial trust is likely to improve the adoption of internet banking services (IBS). This study aims identify the factors that affect customer's initial trust for the adoption of internet banking services in developing countries. Data from a survey of 540 respondents were collected to empirically test the proposed research model. The results of this study show that organisational structural assurance, banks' reputation, perceived relative advantages, and uncertainty avoidance are the most important determinants of customers' initial trust in IBS in developing countries. In addition, the results indicate that initial trust in IBS positively influences intention to use IBS. The obtained results underpin the claim that national culture has a significant role in forming customers' initial trust in IBS, particularly in developing countries' context.